Extracción de arcilla, sus implicaciones ambientales y socioeconómicas y propuesta de cierre en yacimientos Villa Pucayacu, Loreto 2024 - Guerra Mozombite, Adita Anali (2025)
The work was developed in Villa Saint John the Baptist Pucayacu District, with the purpose of determining the clay extraction and its environmental and socioeconomic implicancias, the study was prospective, the universe conformed it 18 people among (administrative personnel, workers and of allotment), the sample conformed it 18 people, for the dependability of the applied instrument (it interviews) it was determined through the test of Alpha of Cronbach, being reached the conclusion: The clay extraction doesn't fulfill the Normative one effective of remediación that has to be carried out in these activities, the company has operation license this affirms it the (100%) sent by the competent entities of the region, social conflicts exist with alive people of the area, they use light machineries (100%), the practices of environmental restoration are little (55.6%), they have a frequency of exploitation of the location from 3 to 6 times daily (100%). significant changes Exist in the topography of the land (66.7%), the erosion of the floor is very high (55.6%), the loss of the hábitat (55.6%), the impact to the near basins is high (44.4%), the landscape of the area is affected in a (72.2%), the lost of the vegetable covering is high (44.4%). partly economic the company has a significant effect (72.2%), generating direct employment (77.8%) and the level of the population's environmental conscience is high (44.4%).